The Lutheran Confessions in Korea - Eom, Jin-Seop (Dialog, 2006)
Although Christianity has been active in Korea for two centuries, the church of the Lutheran confessions was planted only a half century ago, in 1958, by the Lutheran Church-Missouri Synod. With an ecumenical face, Korean Lutherans provide a dynamic leaven in wider society and the church is growing. Even though other Korean church bodies have engaged in writing new confessional statements, Lutherans are finding the richness of the Lutheran Confessions in the Book of Concord sufficient for self-understanding and expansion.